Recursive Equilibria in Dynamic Economies With Stochastic Production - Brumm, Johannes; Kryczka, Dominika; Kubler, Felix (Econometrica, 2017)
In this paper we prove the existence of recursive equilibria in stochastic production economies with infinitely lived agents and incomplete financial markets. We consider a general dynamic model with several commodities, which encompasses heterogeneous agent versions of both the Lucas asset pricing model and the stochastic neo-classical growth model as special cases. Our main assumption is that there are atomless shocks to fundamentals that have a purely transitory component and a component that does not depend on last period's shocks directly.